Thank you for registering.

One of our academic counsellors will contact you within 1 working day.

Please check your email for login details.
MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM
DETAILS
MRP
DISCOUNT
FINAL PRICE
Total Price: Rs.

There are no items in this cart.
Continue Shopping

If a,b,c are respectively the Pth,Qth and Rth terms of G.P show that (q-r) log a + (r-p) log b + (p-q) c = 0.

If a,b,c are respectively the Pth,Qth and Rth terms of G.P show that (q-r) log a + (r-p) log b + (p-q) c = 0.

Grade:11

1 Answers

Arun
25763 Points
3 years ago

Let A and R be the first term and common ratio of G.P. respectively.

n th term of G.P., an = AR – 1

p th term of G.P. = a

∴ AR p – 1 = a ...(1)

q th term of G.P. = b

∴ AR q – 1 = ...(2)

r th term of G.P. = c

∴ AR r – 1 = c ...(3)

aq-r br-p cp-q

 whe we put the value, we get

aq-r br-p cp-q = 1

Now taking log

(q-r) log a + (r-p) log b + (p-q) c = log 1

(q-r) log a + (r-p) log b + (p-q) c = 0

Hence proved

Think You Can Provide A Better Answer ?

Provide a better Answer & Earn Cool Goodies See our forum point policy

ASK QUESTION

Get your questions answered by the expert for free